ACCOUNTING AND TAX REPORTING OF FINANCIAL RESULTS (Mongolian Journal of Agricultural Sciences, 2015)
This article presents a synthetic and analytical accounting of financial result from the sale of products and the final financial result; reflects the operational and non-operating income and expenses from fines, penalties. And, also in this paper, we consider the differences, similarities and the interaction of tax and accounting.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 141-145